Mapping the cervical cancer screening cascade among women living with HIV in Johannesburg, South Africaa. Issue 1 (11th December 2020) - Rohner, Eliane; Mulongo, Masangu; Pasipamire, Tafadzwa; Oberlin, Austin M.; Goeieman, Bridgette; Williams, Sophie; Lubeya, Mwansa K.; Rahangdale, Lisa; Chibwesha, Carla J.
Abstract: Objective: To map the cervical cancer screening cascade among women living with HIV attending a public‐sector cytology screening program in Johannesburg, South Africa. Methods: We conducted a retrospective cohort study of routinely collected clinical data captured in an electronic medical record system. Women (≥18 years) living with HIV with an abnormal Pap result between January 2013 and May 2018 were included. The proportion of women who received follow‐up consistent with extant clinical guidelines, stratified by their initial Pap smear result, was examined. Results: The study included 2072 women: 1384 (66.8%) with a low‐risk Pap result, 681 (32.9%) with a high‐risk Pap result, and 7 (0.3%) with suspected cancer. Only 174 (25.6%) women with a high‐risk Pap result underwent guideline‐indicated management within 18 months. Among women with a low‐risk Pap result, 375 (27.1%) received follow‐up within 1 year; the cumulative incidence of follow‐up increased to 63.1% at 3 years. All women with suspected cancer either received a colposcopic biopsy or were referred for further treatment. Conclusion: Attrition among South African women living with HIV who attended cervical screening in an urban public‐sector program was high. Developing tailored interventions to address bottlenecks in the care cascade and improve cervical screening outcomes will be central to eliminating cervical cancer. Abstract : Investment in program monitoring is needed to identify gaps in the cervical screening cascade and develop interventions to improve outcomes for women living with HIV.